Albert Jóhannesson and the scribes of Hecla Island: Manuscript culture and scribal production in an Icelandic-Canadian settlement - Katelin Parsons (2019)
Manuscript culture in Icelandic immigrant communities in North America is examined through the case study of an immigrant-scribe, Albert Jóhannesson (1847–1921), who left Iceland as an adult in 1884 and eventually settled in the community of Hecla Island, Manitoba, Canada. Albert Jóhannesson is one of the last known individuals in the Icelandic tradition to participate in manuscript production as a pastime: he started his oldest saga manuscript in 1889, and his last dated saga is from 1910. He copied some material from printed books and periodicals but worked mainly from manuscript exemplars borrowed from fellow immigrants. At least one of Albert's exemplars, SÁM 35 from 1827-1829, was brought to Canada by another Hecla Islander, Grímólfur Ólafsson (1827–1903), and contains an abridgement of Breta sögur, the concise Old-Norse Icelandic version of Geoffrey of Monmouth's Historia regum Britanniae. Albert's manuscripts contain a diverse mixture of Old Norse-Icelandic literature, medieval romances, pseudohistory, younger prose romances derived from rímur poetry and 19th-century literature in Icelandic translation. Sagas of settlement are conspicuously absent, however. Albert grew up in dire poverty, and his experiences as an immigrant prior to moving to Hecla Island included what would today be defined as human trafficking. Albert's experiences deeply impact his scribal activities, and instances can be found where he choses to depart dramatically from his exemplars, particularly where they deal with children encountering hardship or danger. Far from being an eccentric hermit in the bush, Albert appears to have been an active participant in a scribal community on Hecla Island. The study demonstrates that scribes operated in collaboration with others in their local Icelandic settlements and made new connections on their arrival to North America that enabled the continued circulation of manuscript material, including medieval works not existing in printed editions.